Intra-breath arterial oxygen oscillations detected by a fast oxygen sensor in an animal model of acute respiratory distress syndrome - Formenti, F; Chen, R; McPeak, H; Murison, P; Matejovic, M; Hahn, C; Farmery, A (Oxford University Press, 2015)
Background There is considerable interest in oxygen partial pressure (Po2) monitoring in physiology, and in tracking PO2 changes dynamically when it varies rapidly. For example, arterial PO2 (PaO2) can vary within the respiratory cycle in cyclical atelectasis (CA), where PaO2 is thought to increase and decrease during inspiration and expiration, respectively. A sensor that detects these PaO2 oscillations could become a useful diagnostic tool of CA during acute respiratory distress syndrome (ARDS). Methods We developed a fibreoptic PO2 sensor (<200 µm diameter), suitable for human use, that has a fast response time, and can measure PO2 continuously in blood. By altering the inspired fraction of oxygen (FIO2) from 21 to 100% in four healthy animal models, we determined the linearity of the sensor's signal over a wide range of PaO2 values in vivo. We also hypothesized that the sensor could measure rapid intra-breath PaO2 oscillations in a large animal model of ARDS. Results In the healthy animal models, PaO2 responses to changes in FIO2 were in agreement with conventional intermittent blood-gas analysis (n=39) for a wide range of PaO2 values, from 10 to 73 kPa. In the animal lavage model of CA, the sensor detected PaO2 oscillations, also at clinically relevant PaO2 levels close to 9 kPa. Conclusions We conclude that these fibreoptic PaO2 sensors have the potential to become a diagnostic tool for CA in ARDS.